2008
DOI: 10.1021/jo801423a
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Spatial Considerations in theN,N′-Diacyl- and Bis(alkoxycarbonyl)bispidinone Series

Abstract: Diamidic and dicarbamic bispidinones show trans-cis isomerism, the relative population in solution of the cis form increasing with solvent polarity. The mutual proximity of the two amide functions in 4a has no impact on the barrier to isomerization. The system represents a peculiar case of planar chirality posing a challenge to its specification.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…20 In CDCl3, the ratio of anti to syn was 3:1, while DMSO favored the structure with high dipole moment, the syn conformer. 24,25 ROESY spectrum confirmed the presence of syn and anticonformers in F3 (Fig. 3a, b).…”
Section: Resultsmentioning
confidence: 53%
“…20 In CDCl3, the ratio of anti to syn was 3:1, while DMSO favored the structure with high dipole moment, the syn conformer. 24,25 ROESY spectrum confirmed the presence of syn and anticonformers in F3 (Fig. 3a, b).…”
Section: Resultsmentioning
confidence: 53%
“…. C separations found in published papers on bispidine bis-amides range from 3.041 [14] to 4.696 Å [13] (here, we compare only the C . .…”
Section: X-ray Studiesmentioning
confidence: 99%
“…These differences the level of rigidity of the bispidine core: while the macrocyclic nature of 3 dicta spatial proximity of the carbonyl groups in the 10-membered ring, the acyclic mole could adopt a more relaxed conformation of the bicyclic core. The values of C…C s tions found in published papers on bispidine bis-amides range from 3.041 [14] to 4 [13] (here, we compare only the C…C distance since O…O separation obviously for the syn-and anti-forms). These findings clearly demonstrate that, in contrast widely known conformational rigidity of the bispidine bicycle in the double-chair c mation, the subtle structural factors could have a pronounced impact on the spatial ture of the molecules, even in the case when a system contains conventionally plan conformationally stable amide moieties.…”
Section: X-ray Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…5 In 2008, planar chirality was observed in bispidinones 2 (R = COMe, R′ = Ph) by Albeck and co-workers through NMR studies. 6 As part of our research on functionalized bisbispidines, 7−9 it was found that bispidines 1 (R = COCH 2 X, R′ = H) exhibit chirality in the absence of chiral centers. Analysis of the molecular structure indicates planar chirality, which has been confirmed by X-ray diffraction studies.…”
Section: ■ Introductionmentioning
confidence: 99%